Do Unit Value Export, Import, and Terms of Trade Indices Represent or Misrepresent Price Indices? - Silver, Mick (IMF Working Papers; Working Paper ;, 2007)
Unit value export and import indices compiled from returns to customs authorities are often used as surrogates for price indices in the measurement of inflation transmission, terms of trade (effects), and to deflate import and export value series to derive volume series. Their widespread use is mainly due to their relatively low cost compared with establishment price surveys. This paper provides evidence of substantial bias in their representation of such price changes. Their continued use would mislead economic analysis. The paper considers the efficacy of alternative strategies for their improvement, and argues for a move to establishment-based price surveys.